Choosing the most appropriate biologic therapy for Crohn's disease according to concomitant extra-intestinal manifestations, comorbidities, or physiologic conditions. (2nd January 2020) - Romano, Ciro; Esposito, Sergio; Ferrara, Roberta; Cuomo, Giovanna
ABSTRACT: Introduction : approximately half of Crohn's disease (CD) patients suffer from concomitant extra-intestinal manifestations (EIMs). Moreover, CD patients may suffer from comorbidities or have physiologic characteristics that may influence the outcome of a biologic treatment. Previous guidelines, published when only TNF-α antagonists were available as biological agents, addressed only management of CD patients with the most common EIMs. Areas covered : Because of the recent introduction of new biologics for the treatment of Crohn's disease as well as increased awareness about comorbidities potentially able to affect the impact of biological drugs, here we provide an update on management considering old and new biologics with proven efficacy on both Crohn's disease and associated conditions, in order to ideally profile the patient to the best of the current knowledge. Expert Opinion : While waiting for identification and validation of widely available and reliable biomarkers able to predict which biologic may yield the best response in the individual IBD patient (rigorous precision medicine), the choice of biologic agents in CD patients in order to achieve the best outcome still lies on a thorough assessment of patient-related characteristics as well as deep knowledge of the properties and place in therapy of each biologic drug.